Name-calling, jealousy, and break-ups: Teen girls' and boys' worst experiences of digital dating. (January 2020) - Reed, Lauren A.; Conn, Kourtney; Wachter, Karin
Highlights: A sample of 262 teens wrote about their worst digital dating experiences. Insults, violations of privacy, break-ups, rumors and pressure for sex/sexual photos were reported. Insults, pressure for sex or sexual photos were particularly salient for girls. Girls were more likely to cry or be upset in response to worst digital experiences. Teens were most likely to tell their peers about their worst digital experiences. Abstract: As the use of social media and mobile phones increase, scholars and practitioners have become concerned about the role these media might play in dating abuse among adolescents. However, less is known about teens' perceptions of various types of digital dating experiences. The current study sought to understand how teens conceptualized their "worst experiences" of digital dating and how they responded to these experiences. A sample of 262 high school students completed an online survey including an open-ended question asking them to write about their "worst" digital dating experience with follow-up questions about how they responded and whom they told about the incident. A content analysis of open-ended responses found that public insults, general insults, violations of privacy, rumors, break-ups, and pressure for sex/sexual photos were the most commonly reported worst digital dating experiences. Responses to digital dating experiences varied by gender, and girls were more likely than boys to cry or be upset. Teens were more likely to tell their peers than trusted adults about their worst digital dating experiences. The implications of these findings for understanding dating abuse is discussed to better inform educators and practitioners working with teens.